2018
DOI: 10.1161/jaha.118.009705
|View full text |Cite
|
Sign up to set email alerts
|

Differential Features of Culprit Intracranial Atherosclerotic Lesions: A Whole‐Brain Vessel Wall Imaging Study in Patients With Acute Ischemic Stroke

Abstract: BackgroundIntracranial atherosclerotic disease tends to affect multiple arterial segments. Using whole‐brain vessel wall imaging, we sought to study the differences in plaque features among various types of plaques in patients with a recent unilateral anterior circulation ischemic stroke.Methods and ResultsSixty‐one patients with unilateral anterior circulation ischemic stroke were referred to undergo whole‐brain vessel wall imaging (before and after contrast) within 1 month of symptom onset for intracranial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…In addition, pathological remodeling of cerebrovasculature has been proved to contribute to poor neuronal repair and worsened cognitive deficits in rats with diabetic stroke (Ward et al, ). In clinical researches, pathological vascular remodeling has been used as an approach and an indicator to evaluate the etiology (Sun & Yuan, ), risk stratification (Wu et al, ) and therapeutic efficacy (Abraham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pathological remodeling of cerebrovasculature has been proved to contribute to poor neuronal repair and worsened cognitive deficits in rats with diabetic stroke (Ward et al, ). In clinical researches, pathological vascular remodeling has been used as an approach and an indicator to evaluate the etiology (Sun & Yuan, ), risk stratification (Wu et al, ) and therapeutic efficacy (Abraham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Varetto et al reported a statistically signi cant correlation between increased vascularization of carotid atherosclerotic plaques evaluated by CEUS and cerebrovascular neurological events [30]. Similarly, Wu et al concluded that strong contrast enhancement can reveal culprit lesions, likely suggesting greater neovascularization and/or in ammatory activity in atherosclerotic lesions [36].…”
Section: Discussionmentioning
confidence: 99%
“…Information on the degree of carotid stenosis was not included in this study. Recent atherosclerosis research has suggested that lumen narrowing may not be a reliable indicator of plaque severity because positive artery remodeling of the vessel wall is associated with the culprit lesions [36,37]. Notably, vulnerable atherosclerotic plaque may suggest an increased risk of cerebrovascular events, even with low-grade carotid narrowing [38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the earlier phase of the positive remodeling of atheromatous plaques development on vessel walls was neglected 12 . Furthermore, the characterization of focal luminal narrowing by probable atheromatous plaques in asymptomatic patients did not allow the definition of adequate primary prevention, due to the impossibility of establishing a real risk 13 . .…”
Section: Intracranial Atheromatous Diseasementioning
confidence: 99%